Development of structures of the aircraft fire alarm system by means of nested modules - Al-Ammouri, Ali; Dmytrychenko, Andrew; Al-Ammori, Hasan; Kharuta, Vitalii (Eastern-European Journal of Enterprise Technologies, 2019)
Optimization of structures of information management systems is determined by the choice of such a functional structure that would ensure high reliability of information. When creating complex systems, there is the problem of ensuring high operational reliability of connection of a large number of separate elements into a single monolithic highly efficient information system. This problem is effectively solved by combining the elements of the system of controlled information sensors by means of nested modules. The mathematical model of parallel information redundancy based on polynomial distribution is developed. This model allows exploring the probability states of the fire alarm system, consisting of n parallel-connected identical sensors. As the state of the fire alarm system, indicators such as probabilities of correct detection, non-detection and false alarm are considered. On the basis of the proposed model, mathematical dependencies of the basic modules М2,3, М2,4 are obtained, taking into account the majority factor, and accordingly schematic diagrams of these modules on logic gates are developed. Mathematical dependences for the first (N6,9, N12,24) and second (L18,27, L48,96) hierarchies of connection of fire alarm system sensors, implementing the majority rule «m-out-of-n», taking into account their hierarchy are obtained. The generalized mathematical formulas for determining the number of logic AND gates in each specific structural circuit for nested modules of the first and second hierarchies, as well as the mathematical formula for n hierarchies, are proposed. Mathematical dependencies of the total economic gain, which consists in reducing the number of AND circuits for implementing the majority rule «m-out-of-n» using nested modules, are obtained. It is advisable to introduce structures of fire alarm systems on the basis of nested modules into production, as the reliability of information increases even with low reliability characteristics of the sensors